2009
DOI: 10.1111/j.1365-2516.2008.01926.x
|View full text |Cite
|
Sign up to set email alerts
|

Patients’, physicians’, and pharmacists’ preferences towards coagulation factor concentrates to treat haemophilia with inhibitors: results from the COHIBA Study

Abstract: Despite modern highly efficacious technologies, there is still a lack of consensus on how to optimally treat haemophilia patients with inhibitors. The aim of the study was to evaluate preferences towards the characteristics of different coagulation factor concentrates for haemophilia inhibitors patients, from the perspective of patients or their caregivers, haematologists and pharmacists. A discrete choice study was conducted. Potential products were described with eight selected characteristics: perceived vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
48
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(54 citation statements)
references
References 62 publications
3
48
1
Order By: Relevance
“…In contrast, in another previous study that examined Italian patients', pharmacists' and physicians' preferences for medication attributes for the treatment of uncomplicated haemophilia, cost and perceived viral safety were the most important considerations for physicians . A similar study of Italian physicians' pharmacists' and patients' preferences for the treatment of patients with inhibitors also found that cost, which was defined as an increase in health care taxes, was the most important attribute to physicians (RI = 25.7%) . Among inhibitor patients (or their caregivers) in this same study, cost (RI = 21.0%), risk of anamnestic response (RI = 20.3%), possibility of undergoing major surgery (RI = 17.9%) and perceived viral safety (RI = 17.7%) were the most important characteristics .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, in another previous study that examined Italian patients', pharmacists' and physicians' preferences for medication attributes for the treatment of uncomplicated haemophilia, cost and perceived viral safety were the most important considerations for physicians . A similar study of Italian physicians' pharmacists' and patients' preferences for the treatment of patients with inhibitors also found that cost, which was defined as an increase in health care taxes, was the most important attribute to physicians (RI = 25.7%) . Among inhibitor patients (or their caregivers) in this same study, cost (RI = 21.0%), risk of anamnestic response (RI = 20.3%), possibility of undergoing major surgery (RI = 17.9%) and perceived viral safety (RI = 17.7%) were the most important characteristics .…”
Section: Discussionmentioning
confidence: 99%
“…A similar study of Italian physicians' pharmacists' and patients' preferences for the treatment of patients with inhibitors also found that cost, which was defined as an increase in health care taxes, was the most important attribute to physicians (RI = 25.7%) . Among inhibitor patients (or their caregivers) in this same study, cost (RI = 21.0%), risk of anamnestic response (RI = 20.3%), possibility of undergoing major surgery (RI = 17.9%) and perceived viral safety (RI = 17.7%) were the most important characteristics . However, consistent with the current study, characteristics related to patient convenience such as the dosage form and frequency of infusions, were of relatively minor importance to both patients and physicians in each of these previous studies .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The management of bleeding episodes in haemophilia patients with high‐titre inhibitors [>5 Bethesda units (BU)] [1] is one of the major challenges in haemophilia care today. The prevalence of inhibitors in patients with haemophilia A varies from 20% to 30% [2]. Although less common, people with haemophilia B may also develop inhibitors (estimates show a prevalence of 2–5%) [2].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of inhibitors in patients with haemophilia A varies from 20% to 30% [2]. Although less common, people with haemophilia B may also develop inhibitors (estimates show a prevalence of 2–5%) [2].…”
Section: Introductionmentioning
confidence: 99%